Health personnel, family relationships and codependency of psychoactive substances: a phenomenological approach - Leone Mendes Dias; Marcelo da Silva Alves; Maria Odete Pereira; Laércio Deleon de Melo; Camila Cristina Gregório de Assis; Thelma Spindola
ABSTRACT Objectives: to reflect on the daily life of family members dependent on psychoactive substances and the role of health professionals in Primary Care. Methods: a descriptive investigation outlined in Maffesoli's phenomenological approach, carried out at a Basic Health Unit in Minas Gerais with eight family members dependent on psychoactive substances. Sociodemographic characterization data and in-depth interviews were collected and analyzed with support of NVivo Pro11® software. All ethical and legal aspects were met. Results: physicians were the professionals most mentioned in participants' statements, who took on a dubious role with other health professionals: welcoming (positive perceptions about care received) and neglect (negative perceptions). Final Considerations: dependence on psychoactive substances imposes a burden on persons, their family members and health professionals. The role of establishing good relationships in the triad professionals-users-family members of primary care is inseparable in favor of treatment and preservation of their mental health.